2008
DOI: 10.1090/s0094-9000-09-00744-3
|View full text |Cite
|
Sign up to set email alerts
|

On some properties of asymptotic quasi-inverse functions

Abstract: We introduce the notions of asymptotic quasi-inverse functions and as-ymptotic inverse functions as weaker versions of (quasi-)inverse functions, and study their main properties. Asymptotic quasi-inverse functions exist in the class of so-called pseudo-regularly varying (PRV) functions, i.e. functions preserving the as-ymptotic equivalence of functions and sequences. On the other hand, asymptotic inverse functions exist in the class of so-called POV functions, i.e., functions with positive order of variation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
1
26
0
3
Order By: Relevance
“…The paper is divided into two parts, Part I containing Sections 1-7, and Part II (see [7]) containing Sections 8-11.…”
Section: F (T)) ∼ T As T → ∞;mentioning
confidence: 99%
“…The paper is divided into two parts, Part I containing Sections 1-7, and Part II (see [7]) containing Sections 8-11.…”
Section: F (T)) ∼ T As T → ∞;mentioning
confidence: 99%
“…The third part of this paper (Sections 4-6) deals with some properties of functions preserving the equivalence of functions, that is with functions f satisfying f (u(t))/f (v(t)) → 1, whenever u(t)/v(t) → 1 (as t → ∞), and with asymptotic quasi-inverse functions (confer Buldygin et al [9], [15]- [17]; proofs can be found in [11] and [15]- [17]). This part is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…PRV functions and their various applications have been studied by Korenblyum [36], Matuszewska [38], Matuszewska and Orlicz [39], Stadtmüller and Trautner [48], [49], Berman [4,5], Yakymiv [53,54], Cline [19], Klesov et al [33], Djurčić and Torgašev [21], Buldygin et al [9], [11]- [13], [15]- [18]. Note that PRV functions are called regularly oscillating in Berman [4], weakly oscillating in Yakymiv [53] and intermediate regularly varying in Cline [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations